1987
DOI: 10.1159/000146377
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Innervation of the Uterus in Guinea Pig and Rat

Abstract: The pattern of distribution of cholinergic and adrenergic nerves in the uterus of albino rats and guinea pigs was examined histochemically. In the albino rat, the uterus was found well-innervated by both adrenergic and cholinergic nerves with a clear regional variation. Dense innervation was demonstrated at the tubal and cervical ends of the uterus and in the cervix. Cholinergic nerves supplying the glands were more numerous than the adrenergic nerves which were relatively few. In the guinea-pigs, the uterus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In agreement with previous studies (Adham and Schenk 1969; Moscarini et al 1982;Papka et al 1985;Garfield 1986;Mustafa et al 1987;Prud'homme et al 2000), we observed that cholinergic nerves were extremely sparse in the cephalic portion of the uterine horn but were concentrated in the caudal region, where they formed a well-developed plexus in association with blood vessels and myometrial smooth muscle. This regional pattern of distribution clearly contrasts with that shown by sympathetic (Adham and Schenk 1969;Houdeau et al 1998;Zoubina et al 1998) and sensory nerve fibers (Zoubina et al 1998), which appear more concentrated in the cephalic portion of the uterine horn.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies (Adham and Schenk 1969; Moscarini et al 1982;Papka et al 1985;Garfield 1986;Mustafa et al 1987;Prud'homme et al 2000), we observed that cholinergic nerves were extremely sparse in the cephalic portion of the uterine horn but were concentrated in the caudal region, where they formed a well-developed plexus in association with blood vessels and myometrial smooth muscle. This regional pattern of distribution clearly contrasts with that shown by sympathetic (Adham and Schenk 1969;Houdeau et al 1998;Zoubina et al 1998) and sensory nerve fibers (Zoubina et al 1998), which appear more concentrated in the cephalic portion of the uterine horn.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike reports for the PG, descriptions of the cholinergic innervation of the uterine cervix and horns are more consistent; some report a dense nerve supply to the myometrium, basal epithelium and glands (Mustafa et al 1987), dense supply to vasculature and myometrium (Kanerva et al 1972b;Garfield 1986) and especially the cervix (M盲kel盲 and Gr枚nroos 1959;Papka et al 1985;Melo and Machado 1993;Sullivan et al 1994). In addition, bilateral destruction of the PG causes loss of AChE-positive fibers from the rat uterine myometrium and perivascular space, indicating that the PG is a major source of such fibers (Kanerva et al 1972b).…”
Section: Cholinergic Elements In the Uterusmentioning
confidence: 90%
“…For example, Kanerva (1971) reported intense AChE activity in one-fifth to one-third of the PG neurons, but Papka et al (1987) and Sullivan et al (1994) reported that the majority of PG neurons were AChEpositive and "cholinergic." "Cholinergic" innnervation of the rat uterine cervix and horns is described as moderate to dense in the myometrium and vasculature, moderate to weak in the endometrium, and with thick branching nerve trunks (Kanerva et al 1972b;Papka et al 1985;Garfield 1986;Mustafa et al 1987;Melo and Machado 1993). Consequently, the cholinergic innervation of the uterus has not been precisely elucidated because of variable results of nonspecific histochemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…These nerves are particularly well developed in the tubo-uterine junction, suggesting a role in sphincter control (Moustafa et al, 1987). Oviductal efferent nerves express a range of neuropeptides including neuropeptide Y (NPY) and vasoactive intestinal polypeptide (VIP) and peptide histidine isoleucine (PHI), (Helm et al, 1982; Papka et al, 1985; Kannisto et al, 1986; Owman et al, 1986b; Czaja et al, 1996).…”
Section: Innervation Of the Female Reproductive Tract: An Overviewmentioning
confidence: 99%
“…There is considerable interspecies variation in the density of uterine cholinergic nerves, being well-develop in mice and humans but almost absent in the guinea pig (Moustafa et al, 1987). NPY co-localizes with acetylcholine (Ach) in neurons of the paracervical ganglia innervating the cervix (Traurig and Papka, 1993).…”
Section: Innervation Of the Female Reproductive Tract: An Overviewmentioning
confidence: 99%